Primary hepatocyte imaging by multiphoton luminescent graphene quantum dots1. Issue 38 (11th May 2015) - Song, Sung Ho; Jang, Min-Ho; Jeong, Jong-Min; Yoon, Hyewon; Cho, Yong-Hoon; Jeong, Won-Il; Kim, Bo-Hyun; Jeon, Seokwoo
<x xml:space="preserve">Abstract</x> We demonstrate a successful application of water soluble graphene quantum dots for multiphoton fluorescence imaging of primary hepatocytes.